2015
DOI: 10.1002/ctpp.201400103
|View full text |Cite
|
Sign up to set email alerts
|

Pressure in electronically excited warm dense metals

Abstract: Non-equilibrium two-temperature warm dense metals consist of the ion subsystem that is subjected to structural transitions and involved in the mass transfer, and the electron subsystem that in various pulsed experiments absorbs energy and then evolves together with ions to equilibrium. Definition of pressure in such non-equilibrium systems causes certain controversy. In this work we make an attempt to clarify this definition that is vital for proper description of the whole relaxation process. Using the densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The question about the electron pressure description is a crucial aspect of simulation for gold. 30,52,53 Inclusion of the electron pressure in the model leads to the short type of ablation. At the same time, the detailed experimental study of the dependence of surface morphology on absorbed energy is not carried out for single laser pulse.…”
Section: B Simulation Of Ablation In Goldmentioning
confidence: 99%
“…The question about the electron pressure description is a crucial aspect of simulation for gold. 30,52,53 Inclusion of the electron pressure in the model leads to the short type of ablation. At the same time, the detailed experimental study of the dependence of surface morphology on absorbed energy is not carried out for single laser pulse.…”
Section: B Simulation Of Ablation In Goldmentioning
confidence: 99%
“…23 Therefore, in case of metals, where many electrons with good mobility exist, we expect that the explanation based on the CE model should be replaced by the former explanation. Although these previous studies have suggested that a large contribution of the force induced by change of the electronic states originates from the kinetic energy of free (delocalized) electrons, 18,19,24,25 the validity of this explanation has yet to be clarified. Furthermore, comparison with experimental results has not been performed sufficiently.…”
mentioning
confidence: 97%
“…Although these previous studies have suggested that a large force contribution induced by changes in the electronic states originates from the kinetic energy of free (delocalized) electrons. 18,19,24,25) The validity of this explanation has yet to be clarified. Furthermore, a sufficient comparison with experimental results has not been performed.…”
mentioning
confidence: 99%
“…Films thinner than thickness of a heat affected zone d T are called thin here (for gold d T ≈ 150 nm). Their dynamics, freezing at late times, and structures fixed during the freezing processes are qualitatively different from those which correspond to the bulk targets; onedimensional (1D) dynamics of bulk targets was studied in papers [33][34][35][36][37][38][39][40][41]. The thin films are considered in the presented paper.…”
Section: General Viewmentioning
confidence: 99%